Redefining Competency Based Education : Competence for Life - Jones Morel, Nina; Griffiths, Bruce (Human resource management and organizational behavior collection., 2018)
Redefining Competency-Based Education provides an expanded definition of career competence, based on actual employer hiring and promotion requirements, which enhances university curricula to better prepare students for work and life. Readers will learn how private sector competency models have evolved to define criteria for hiring, promoting, and training talent. The authors contrast these models with classic university practices to document a historic academic preference for technical preparation over the so-called soft skills valued by employers. This book outlines techniques for measuring and developing soft skills that provide significant advantage in career success, and shares examples of universities that have successfully implemented these concepts.